2018
DOI: 10.12659/msm.906250
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Stimulates Hepatitis B Virus (HBV) Replication Through Autophagy

Abstract: BackgroundReactivation of hepatitis B virus (HBV) is a fatal complication of chemotherapy. Occult HBV infection might be reactivated in patients undergoing chemotherapy or immunosuppression. However, the mechanism of HBV reactivation induced by chemotherapy or immunosuppression remains unclear.Material/MethodsHepG2.2.15 cells were treated with an autophagy inducer (rapamycin), an inhibitor (3-methyladenine, 3-MA), and dexamethasone. Autophagosomes were observed by a transmission electron microscope (TEM). LC3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…In chronic infection, HBV can activate autophagy through different pathways, 100 promoting the replication of HBV and the formation and release of virus particles, thus aggravating the disease process. [101][102][103] For example, HBs can activate autophagy by triggering endoplasmic reticulum stress. 104 HBx can enhance autophagy and promote viral replication by binding to PI3KC3 or by activating miR-192-3p-XIAP signaling.…”
Section: Hbv and Autophagymentioning
confidence: 99%
“…In chronic infection, HBV can activate autophagy through different pathways, 100 promoting the replication of HBV and the formation and release of virus particles, thus aggravating the disease process. [101][102][103] For example, HBs can activate autophagy by triggering endoplasmic reticulum stress. 104 HBx can enhance autophagy and promote viral replication by binding to PI3KC3 or by activating miR-192-3p-XIAP signaling.…”
Section: Hbv and Autophagymentioning
confidence: 99%
“…miR‐155 has been shown to contribute to other processes, including immune and inflammatory reactions, and it was discovered that ectopic miR‐155 expression could eliminate HIV in macrophages arising from monocytes . Sarkar reported that ectopic expression of miR‐155 in HepG2.2.15 cells reduced viral DNA as well as protein titre, and Su reported that miR‐155 enhances innate antiviral immunity through promoting JAK/STAT signalling pathway by targeting SOCS1 and mildly inhibits HBV infection in human hepatoma cells . Our study shows that miR‐155 expression was remarkably inhibited in HepG2 cells transfected with 1.3× copy of an HBV‐containing plasmid, when compared with control cells.…”
Section: Discussionmentioning
confidence: 90%
“…During pregnancy, high concentration of adrenal corticosteroids may in luence the increase in HBV viraemia [11,12]. In most pregnant women with HBV infections and absent HBeAg, viraemia is stable.…”
Section: Discussionmentioning
confidence: 99%